Gastroscopic screening in 80 patients with pernicious anaemia. Issue 12 (December 1983) - Stockbrügger, R W; Menon, G G; Beilby, J O; Mason, R R; Cotton, P B
Abstract : We have studied 80 patients with pernicious anaemia. Upper gastrointestinal endoscopy (with biopsy and cytology) showed no lesion other than atrophic gastritis in 34 patients. Thirty three patients, however, had varying degrees of gastric mucosal dysplasia, which was detected more frequently by histology than by cytology. The endoscopic appearance of the mucosa was abnormal in four of the six patients with moderate dysplasia, and in all three patients with severe dysplasia. One patient was found to have a small carcinoma in the gastric antrum, and underwent total gastrectomy; 18 patients had polyps (often multiple); four of these were treated by endoscopic polypectomy. One of the patients with polyps had multiple carcinoid tumours, and an asymptomatic parathyroid adenoma. Seventeen of the patients also underwent barium meal examination; abnormalities were revealed in only three of the seven patients with lesions visible at endoscopy. Our results justify further endoscopic studies in patients with pernicious anaemia, and sequential examinations to establish the natural history of gastric dysplasia.